2011
DOI: 10.1016/j.jep.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Acalypha wilkesiana extracts induce apoptosis by causing single strand and double strand DNA breaks

Abstract: The extracts (especially ethyl acetate and hexane) of Acalypha wilkesiana possess valuable cytotoxic effects that trigger apoptosis in U87MG and A549 cancer cells through induction of DNA SSBs and DSBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 59 publications
(67 reference statements)
3
28
0
Order By: Relevance
“…The palm oil derived alpha-, gamma- and delta-tocotrienol isomers were extracted and supplied in palm vitamin E isomers kit by Davos Life Science Pte Ltd (Singapore). The human lung adenocarcinoma (A549), grade IV glioblastoma (U87MG) and normal lung fibroblast (MRC5) were grown and maintained at the similar conditions as previously published papers [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The palm oil derived alpha-, gamma- and delta-tocotrienol isomers were extracted and supplied in palm vitamin E isomers kit by Davos Life Science Pte Ltd (Singapore). The human lung adenocarcinoma (A549), grade IV glioblastoma (U87MG) and normal lung fibroblast (MRC5) were grown and maintained at the similar conditions as previously published papers [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the plant is also used to treat malaria, gastrointestinal problems [9], and potentially cancers [10, 11]. Previously, we found anti-MRSA and other antibacterial activities in the ethyl acetate and ethanol extracts of A. wilkesiana [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, A. cuspidata showed a MIC value of 97.65 µg/mL against S. aureus and catalytic antitopoisomerase II activity (at 50 μg/mL). The antitopoisomerase activity of Acalypha genus has not been described, although there is a report about the probable antitopoisomerase II activity of A. wilkesiana extracts, which induce apoptosis by single and double strand DNA breaks (Lim et al, 2011). Chemical studies of the Acalypha genus demonstrated the presence of sesquiterpenes and diterpenes (Siems et al, 1996).…”
Section: Discussionmentioning
confidence: 99%